Mn-modification effects on Nb2O5 structural, optical and vibrational properties (2017)
In this study Mn-modification (at 1%, 2.5%, 5% and 10%) on Nb2O5 was carried out through the Pechini method; the annealing temperatures: 400°C, 500°C, 600°C and 700°C, were used to study the thermal stability of the system and the crystalline growth. The crystallization at high temperatures has been investigated because low annealing temperature cannot improve the crystallization and the effect of Mn-modification concentration is worthy of a further investigation. Before annealing the samples were analysed by TGA. The structural analysis through XRD is carried out to study a possible increase of the crystallite size (L) by increasing the Mn concentration; for the samples at 700°C and 1% and 2.5% concentrations, L is increased from 39.81 to 46.45nm while L changes from 32.67 to 35.63 with 5% and 10%, respectively. After Mn-modification the evolution of (100) and (180) peaks Nb2O5 was observed suggesting that they were well defined only until 2.5%. IR and Raman spectroscopies allowed to analyse vibrational modes present in the samples: the IR spectrums for the samples at 400°C, 500°C and 600°C showed a band around 1100cm-1 which can be associated to C-C(νC-C) and C-O(νC-O) vibrations; at 700°C the shoulder was distinguished around 750cm-1 characteristics of the Nb2O5 orthorhombic structure. Vibration modes associated with Nb2O5 were found with the Raman spectroscopy; these become less intense after Mn-modification. The band gap energy was obtained through UV-Vis spectrophotometry which revealed a slight increase at 700°C.